2015
DOI: 10.1007/s00381-015-2638-1
|View full text |Cite
|
Sign up to set email alerts
|

Schizencephaly—diagnostics and clinical dilemmas

Abstract: BackgroundSchizencephaly is an uncommon congenital disorder of cerebral cortical development. The defect is characterized by the presence of a cleft in the brain extending from the surface of the pia mater to the cerebral ventricles. The margins of the cleft are lined with heterotropic, dysplastic gray matter. The causes of schizencephaly are heterogeneous and can include teratogens, prenatal infection, maternal trauma, or EMX2 mutations.MethodIn the present paper, the authors described difficulties in employi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 16 publications
0
49
0
10
Order By: Relevance
“…1e4 Although several studies have reported that unilateral schizencephaly is slightly more common than bilateral clefts, 8,12 other studies have reported that bilateral schizencephalies are slightly more common or as common as unilateral cleft. 1,2 In our case series, unilateral schizencephaly was more common than bilateral schizencephalies (16:5). In addition, previous studies have reported that bilateral open-lip (60%) is more common in bilateral schizencephalies, and that open-lip (60%) is more common in unilateral cleft.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…1e4 Although several studies have reported that unilateral schizencephaly is slightly more common than bilateral clefts, 8,12 other studies have reported that bilateral schizencephalies are slightly more common or as common as unilateral cleft. 1,2 In our case series, unilateral schizencephaly was more common than bilateral schizencephalies (16:5). In addition, previous studies have reported that bilateral open-lip (60%) is more common in bilateral schizencephalies, and that open-lip (60%) is more common in unilateral cleft.…”
Section: Discussionmentioning
confidence: 59%
“…In addition, previous studies have reported that bilateral open-lip (60%) is more common in bilateral schizencephalies, and that open-lip (60%) is more common in unilateral cleft. 1,8 In our case series, bilateral open-lip (80%) occurred more commonly in bilateral clefts, whereas open-lip and closedlip occurred equally as commonly in unilateral cleft. The clinical features of schizencephaly are extremely variable.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Es el defecto congénito en el que se forman hendiduras en la corteza cerebral. [26][27][28] Se las divide en labio abierto o cerrado según la proximidad de sus labios separados por LCR 26 (►Fig. 20).…”
Section: ) Quiste De La Cisura (Fisura) Coroideaunclassified